2020
DOI: 10.1089/neu.2019.6591
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Blast Exposure: A Functional Study in Rats Using an Advanced Blast Simulator

Abstract: Anecdotal observations of blast victims indicate that significant neuropathological and neurobehavioral defects may develop at later stages of life. To pre-clinically model this phenomenon, we have examined neurobehavioral changes in rats up to 1 year after exposure to single and tightly coupled repeated blasts using an advanced blast simulator. Neurobehavioral changes were monitored at acute, sub-acute, and chronic time-points using Morris water maze test of spatial learning and memory, novel object recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 54 publications
5
48
1
Order By: Relevance
“…To yield a range of overpressure exposures in these experiments, we used Valmax or Acetate membranes yielding peak positive static pressures within the range of 8.5 to approximately 19 psi with a positive phase duration of 3-5msec. The critical biomechanical loading to the experimental subject was determined from both the static (Ps) and dynamic pressures (Pd) of the BOP wave, which are fully recorded by a combination of side-on and head-on piezoresistive pressure gauges (Endevco, Troy, IN) using an Astro-med tmx-18 acquisition system at a 800,000 Hz sampling rate 11,18 . Following 4% isoflurane anesthesia for 6 min, animals (n = 6 per group) were exposed to either a single exposure (1 ×), 2 exposures (2 ×; one daily exposure), 3 exposures (3 ×; one daily exposure), or 4 exposures (4 ×; one daily exposure) to assess the extent of gross lung injury as the primary outcome dependent measure 19 .…”
Section: Methodsmentioning
confidence: 99%
“…To yield a range of overpressure exposures in these experiments, we used Valmax or Acetate membranes yielding peak positive static pressures within the range of 8.5 to approximately 19 psi with a positive phase duration of 3-5msec. The critical biomechanical loading to the experimental subject was determined from both the static (Ps) and dynamic pressures (Pd) of the BOP wave, which are fully recorded by a combination of side-on and head-on piezoresistive pressure gauges (Endevco, Troy, IN) using an Astro-med tmx-18 acquisition system at a 800,000 Hz sampling rate 11,18 . Following 4% isoflurane anesthesia for 6 min, animals (n = 6 per group) were exposed to either a single exposure (1 ×), 2 exposures (2 ×; one daily exposure), 3 exposures (3 ×; one daily exposure), or 4 exposures (4 ×; one daily exposure) to assess the extent of gross lung injury as the primary outcome dependent measure 19 .…”
Section: Methodsmentioning
confidence: 99%
“…Blast waves are known to cause inner ear damage but recent debates question whether the injury is more widespread, and whether various brain regions are being affected by bTBI contributing to neurosensation deficits ( 47 , 48 ). Arun et al found significant neuromotor impairments occurring up to 6 months following repeated blast exposures in rats ( 49 ). As neurobehavioral deficits are being presented following blast exposure, identifying and studying the pathological changes that contribute to these shortfalls is imperative.…”
Section: Introductionmentioning
confidence: 99%
“…Blast-induced acute auditory injuries are associated with an increased risk of chronic hearing loss. To elucidate the mechanisms of transition from acute to chronic injury, we identified ear structural changes and molecular alterations in rats exposed to tightly coupled repeated blast shockwaves 20 . Exposure to tightly coupled blasts is not uncommon either operationally or in military training and generates a more robust injury to the central nervous system which is relatively free of confounding polytrauma than is possible with a single higher amplitude blast wave exposure.…”
Section: Discussionmentioning
confidence: 99%
“…For tightly coupled repeated blast exposures, the animals were exposed to two 16 psi blast overpressure waves separated by 2 min. Exposure to repeated shock waves in this manner is not uncommon either operationally or in military training and generates a more robust insult to the central nervous system that is relatively free of complicating polytrauma than is possible with a single exposure to a higher amplitude waveform 20,54 . The blast overpressure (peak static pressure of 16 psi and ~ 4 ms positive phase duration) was generated by rupture of a VALMEX (Mehler Technologies) membrane mounted in an advanced blast simulator (ABS), which consists of a 0.5 ft. long compression chamber that is separated by the membrane from a 21 ft. long transition/expansion test section (Fig.…”
Section: Methodsmentioning
confidence: 99%